Yahoo Answers จะปิดใช้งานในวันที่ 4 พฤษภาคม 2021 (เวลาตะวันออก) และตอนนี้เว็บไซต์ Yahoo Answers จะอยู่ในโหมดอ่านอย่างเดียว คุณสมบัติหรือบริการอื่นๆ ของ Yahoo หรือบัญชี Yahoo ของคุณจะไม่มีการเปลี่ยนแปลงใดๆ คุณสามารถค้นหาข้อมูลเพิ่มเติมเกี่ยวกับการปิดใช้งาน Yahoo Answers และวิธีการดาวน์โหลดข้อมูลของคุณในหน้าความช่วยเหลือนี้
The solution an algebraic equation.?
Find the time t. A=P(1+r/n)^(nt), where
A=the amount after nt
P=the initial deposit
r=the annual rate of interest
n=the number of intervals in a year & n->infinity
when A=2P? Help please.
4 คำตอบ
- ?Lv 71 สัปดาห์ ที่ผ่านมาคำตอบที่โปรดปราน
It would be useful to memorize the following:
lim (1 + 1/x)^x = e
x→∞
let x = n/r
(1+r/n)^(nt) = (1 + 1/x)^(xrt)
= ((1 + 1/x)^(x))^(rt)
lim ((1 + 1/x)^(x))^(rt) = e^(rt)
x→∞
Thus
2P = Pe^(rt)
t = ln(2)/r
Because ln(2) is approximately 70% (and less-frequent compounding increases t), this leads to the "Rule of 72": for a given rate of return r%, your investment will double in approximately 70/r or 72/r years.
- PinkgreenLv 71 สัปดาห์ ที่ผ่านมา
A=P(1+r/n)^(nt)
=>
ln(A)=ln(P)+ntln(1+r/n)
=>
ln(A/P)=ln(1+r/n)/[1/(nt)]
=>
ln(A/P)->[1/(1+r/n)](-r/n^2)/[(-1/n^2)/t]
as n->infinity
=>
ln(A/P)->rt
=>
A=Pe^(rt)
When A=2P
2P=Pe^(rt)
=>
t=ln(2)/r
[Note that dependence of memorizing
formula is not a goodway because there
are a lot , a lot of formula in math! It is
a good habit to derive formula as much
as possible when needed. Of course,
some basic formulas are needed to
remember as the basis]
- llafferLv 71 สัปดาห์ ที่ผ่านมา
I'm not sure what you are asking.
If you are saying to solve for t from:
A = P(1 + r/n)^(nt)
and A = 2P, then we can do the substitution first, then divide both sides by P:
2P = P(1 + r/n)^(nt)
2 = (1 + r/n)^(nt)
Now get the log of both sides:
ln(2) = ln[(1 + r/n)^(nt)]
we can pull the exponent out of the log:
ln(2) = nt ln(1 + r/n)
And divide both sides by [n ln(1 + r/n)]:
ln(2) / [n ln(1 + r/n)] = t
- Engr. RonaldLv 71 สัปดาห์ ที่ผ่านมา
A=P(1+r/n)^(nt)
2P = P(1 + r/n)^(nt)
(1 + r/n)^(nt) = 2P/P
(1 + r/n)^(nt) = 2
ntln(1 + r/n) = ln(2)
...........ln(2)
t = ------------------
........nln(1 + r/n)
........... ln(2)
t = ----------------------- Answer//
.......... nln[(n + r)/n]